Climate change driven hyposalinity as a selective agent in the littoral mesoherbivore Idotea balthica - Rugiu Luca; de Wit Pierre; Kostian Iita; Jormalainen Veijo (ELSEVIER SCI LTD, 2022)
Climate change will include a decrease in seawater salinity in the Baltic Sea. We quantified the effects of the projected future desalination on survival of the early life stage of the littoral herbivore Idotea balthica. We collected egg-bearing Idotea from three range-margin Baltic Sea populations, we exposed half of each brood to either current (6 parts per thousand) or future salinity (3.5 parts per thousand). We genotyped a subsample of each brood to analyse patterns of allelic change and to identify genomic regions targeted by selection. The survival was overall reduced by hyposalinity and broods varied in response to hyposalinity implying genetic variation in tolerance, with a stronger decrease in genetic diversity in future salinity. Finally, we identified proteins with crucial roles in basic cellular functions. This study indicates that projected future northern Baltic Sea hyposalinity will not just hamper I. balthica survival, but its selective pressure may also affect genetic diversity and cell physiology.